Bioengineering : A Conceptual Approach - Pavlovic, Mirjana (Springer International Publishing : Imprint: Springer, 2015)
This book explores critical principles and new concepts in bioengineering, integrating the biological, physical and chemical laws and principles that provide a foundation for the field. Both biological and engineering perspectives are included, with key topics such as the physical-chemical properties of cells, tissues and organs; principles of molecules; composition and interplay in physiological scenarios; and the complex physiological functions of heart, neuronal cells, muscle cells and tissues. Chapters evaluate the emerging fields of nanotechnology, drug delivery concepts, biomaterials, and regenerative therapy. The leading individuals and events are introduced along with their critical research. Bioengineering: A Conceptual Approach is a valuable resource for professionals or researchers interested in understanding the central elements of bioengineering. Advanced-level students in biomedical engineering and computer science will also find this book valuable as a secondary textbook or reference.